Análise da estabilidade de sistemas de potência via ATP e comparação dos resultados com o PSAT - Ferreira, Gislene Cristiane de Lima (2012)
This study had as main objective to perform the modeling and analysis of transient stability of a typical electric power system. The second goal, also important, was to assess the feasibility of using ATP (Alternative Transients Program) as a computer tool for simulation of transient stability. The system focused here is comprised of nine busses with three generators, one hydraulic and the other two with thermal characteristics. All the system machines were equipped with voltage regulators and speed governor in ATP software. The technical issues studied here refer to the analysis of system stability after a disturbance, such as: three-phase short-circuit, load loss and generation outage. The results show that ATP software performs satisfactorily the transient stability analysis. This fact can also be proved by comparing the results obtained from ATP with those from simulations with PSAT (Power System Analysis Toolbox). For this purpose some adjustments were necessary in the graphical results since ATP works in time domain while PSAT program operates in the frequency domain.